Cultural trauma and the politics of access to higher education in Syria. Issue 4 (4th July 2021) - Al Azmeh, Zeina; Dillabough, Joanne; Fimyar, Olena; McLaughlin, Colleen; Abdullateef, Shaher; Aloklah, Wissam Aldien; Mamo, Adnan Rashid; Abdulhafiz, Abdul Hafiz; Al Abdullah, Samir; Al Husien, Yasser; Al Mohamad Al Ibrahim, Ammar; Al Ibrahim, Ziad; et al.
ABSTRACT: This paper examines the relationship between the politics of Higher Education access pertaining to longstanding practices of patrimonial authoritarian politics and the narration of collective trauma. Building on an empirical study of Syrian HE during war, we suggest that a narrative disjuncture within HEIs has a damaging impact not only upon the educational process, HE reconstruction and reform, but also upon the possibility of social reconciliation. This is especially true when access to education and post-graduation opportunities are directly linked to patrimonial favouritism; widespread social inequalities in access and retention; a violent turn in the purging of oppositional academics; a severely exacerbated brain drain linked to political views; and significantly sparser employment opportunities. Building on the study findings, we show how these challenges are linked to ethico-political positioning vis-à-vis the mass movement of 2011 and related cultural trauma narratives. In closing, we suggest that understanding the relationship between HE access and cultural trauma can inform decision-making on HE reconstruction and future reform.